Digestibility of feeds in broiler chicken (Galus galus linnaeus, 1758) in Africa: a review - ATCHADE, Ghislaine Sègbédji Théodora; HOUNDONOUGBO, M. FRÉDÉRIC; CHRYSOSTOME, CHRISTOPHE ACHILLE A. MAHUSSI; MENSAH, Guy Appolinaire (My University, 2019)
Feed digestibility indicates how much the body uses feed and its nutrients. This study aimed at making a literature review on the digestibility of balanced feed given to broiler chicken in Africa. Data used for this literature review were collected through many scientific papers published from 2008 to 2018 and uploaded to Google Scholar, Pubmed, Agora search engines and in national university libraries. Numerous scientific studies in this field indicate that more than forty feedstuffs are commonly used to formulate balanced feed delivered to broiler chicken in modern system in Africa. Feed digestibility is generally assessed in vivo by the direct method in broiler chicken. The data compiled shows that feed digestibility of broiler chicken varies enormously depending on the feedstuffs in balanced feed and also on their incorporation rate. This literature review reveals that balanced feeds used to feed broiler has Apparent Digestibility more than 50%.
Keywords: Balanced feed; In vivo digestibility; Broiler chicken; Africa